Altered global microRNA expression in hepatic stellate cells LX-2 by angiotensin-(1–7) and miRNA-1914-5p identification as regulator of pro-fibrogenic elements and lipid metabolism - de Oliveira da Silva, Brenda [UNESP]; Alberici, Luciane Carla; Ramos, Letícia Ferreira [UNESP]; Silva, Caio Mateus [UNESP]; da Silveira, Marina Bonfogo [UNESP]; Dechant, Carlos R.P.; Friedman, Scott L.; Sakane, Kumiko Koibuchi; Gonçalves, Letícia Rocha [UNESP]; Moraes, Karen C.M. [UNESP] (Elsevier, 2018)
The development of new therapeutic strategies to control or reverse hepatic fibrosis requires thorough knowledge about its molecular and cellular basis. It is known that the heptapeptide angiotensin-(1–7) [ang-(1–7)] can reduce hepatic fibrosis and steatosis in vivo; therefore, it is important to uncover the mechanisms regulating its activity and cellular model of investigation. Ang-(1–7) is a peptide of the renin-angiotensin system (RAS), and here we investigated its modulatory effect on the expression pattern of microRNAs (miRNAs) in hepatic stellate cells (HSCs) LX-2, which transdifferentiate into fibrogenic and proliferative cells. We compared the miRNA profiles between quiesced, activated and ang-(1–7)-treated activated HSCs to identify miRNAs that may regulate their transdifferentiation. Thirteen miRNAs were pointed, and cellular and molecular analyses identified miRNA-1914-5p as a molecule that contributes to the effects of ang-(1–7) on lipid metabolism and on the pro-fibrotic environment control. In our cellular model, we also analyzed the regulators of fatty acid metabolism. Specifically, miRNA-1914-5p regulates the expression of malonyl-CoA decarboxylase (MLYCD) and phosphatidic acid phosphohydrolase (PAP or Lipin-1). Additionally, Lipin-1 was closely correlated with mRNA expression of peroxisome proliferator-activated receptors (PPAR)-α and −γ, which also contribute to lipid homeostasis and to the reduction of TGF-β1 expression. These findings provide a novel link between RAS and lipid metabolism in controlling HSCs activation.
Keywords: Angiotensin-(1–7); HSC fibrogenesis; Lipid metabolism; MicroRNA; Transdifferentiation